Contemporary's practical English writing skills: - Scheraga, Mona (Contemporary Books, 1999)
The book helps students of English further develop the writing skills they need to succeed in school, on the job or at home. This book discusses and explains in a straightforward, helpful manner each type of writing including job applications, cover letters, requesting an interview, essays, bibliographies, résumés, college applications, outlines, note-taking, and research papers.